A missão do Bom Pastor em Jo 10.1-18 : uma análise exegético-teológica - Debatin, Osmar (2011)
There is no doubt about the importance one should give to the words of the Good Shepherd in John 10. Nevertheless, very few studies have dealt with the dynamics of the narrative, its inner structure and especialy, with its relationship within the contex of the fourth gospel. We know even less about the links of this text with others in the Old Testament, what is said in the the Jewish Tradition and other writings betwween the two Testaments. Neediess to say that a close study of these sources will give an exegetical and hermeneutical focus and a new perspective to these words of Jesus. This could also be achieved without overlookin different studies and interpretations os these verses given by worlwide known exegetes.